A DEIXIS ANALYSIS IN WESTLIFE' ''BEAUTIFUL IN WHITE" SONG LYRICS - Sandra Agatha; Ratih Inayah (PROJECT (Professional Journal of English Education), 2022)
One of the most critical studies in pragmatics is deixis. Deixis can be found in a conversation, written text, song lyrics, etc. The aims of this study is to analyze the different forms of deixis used in Beautiful In White song lyrics and determine which ones are the most dominant.  Qualitative research was applied in this research. After analyzing the results, the findings revealed that Beautiful In White song lyrics use five types of deixis, including person deixis, spatial deixis, temporal deixis, social deixis, and discourse deixis, as described by Alan Cruse (2000). Person deixis is the most commonly used deixis in Beautiful In White song lyrics, accounting to 56 deictic words (71.80%), dominated by the word "You". The song lyrics also include other forms of deictic terms, such as spatial deixis 2 deictic words, temporal deixis 15 deictic words, social deixis 1 deictic word, and discourse deixis 4 deictic words. Keywords:  Pragmatic, Deixis, Song Lyrics